Microsystems Mechanical Design - De Bona, Francesco; Enikov, Eniko T. (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2006)
Nowadays, micromechanics (i.e., mechanics of microsystems) is probably one of the most promising and rapidly growing fields among new emerging technologies. In fact, the possibility of reducing the size of mechanical structures to the micro-domain opens a wide variety of possible applications in the biomedical, aeronautical, and automotive fields, in robotics, in molecular engineering, in fiber optics, and infiuidics technology. One of the main aspects that slows down the development of innovative industrial products based on microsystem technology is the existing lack of engineering tools to allow a reliable design of microsystems . The aim of this book is that of collecting the texts o the lectures given at the CISM course on: Microsystems Mechanical Design, hold in July 2004. The purpose of this course was to introduce the basic tools used in the mechanical design of microsystems, the fabrication methods for these systems, and several applications of this technology. The links between micro- and nanotechnologies were also discussed and light was shed on the potential applications of microsystems to nano-scale manipulation of matter, thus introducing the topic of nano-scale engineering mechanics, which will be fully explored in a future course. This book is arranged in 8 sections. In the first section an introduction on microsystems and the techniques for their fabrication will be presented, with a thoroughly description of surface and bulk micromachining techniques and of other microfabrication processes as LIGA and anoding bonding.